Women, Nature and Neocolonial Struggles:Different Perspectives on Indigenous Women’s Position - Casi, Corinna (De Gruyter, 2023)
This article is situated within the gender inequality debate associated with the relation between nature and women, which began to be conceptualized academically in the 1970s in the philosophical field of ecofeminism. After presenting some ecofeminist perspectives highlighting the reasons of the women/nature connection, some criticism will be advanced challenging the invisibility of women’s role and their work in society, showing as well the limitation of such approaches. The argument will then move to the field of Indigenous feminism, keeping the focus of the relation between nature and women, and observing how this has influenced the condition of women within Indigenous communities such as the Igbo people in Nigeria, the Kahnawa:kev people in Canada and the Sami people living in Sapmi, in the North of Europe and Northwest of Russia.